Multimodal treatments and the risk of breast cancer-related lymphedema: insights from a nationally representative cohort in South Korea - Sung Hoon Jeong; Seong Min Chun; Miji Kim; Ye Seol Lee; Jisun Kim; Ja-Ho Leigh; Yoon-Hee Choi (BMC Cancer)
Abstract Background As the roles of chemotherapy (Chemo) and radiation therapy (Radio) in the definitive treatment of breast cancer have expanded, a broader understanding of the factors associated with breast cancer-related lymphedema (BCRL) has become increasingly essential. Therefore, we investigated the association between multimodality treatment and the risk of BCRL. Methods In this retrospective study conducted using National Health Insurance data and the Korea National Cancer Incidence Database (2006–2017), 114,638 participants who underwent Surgery (Surg) or Chemo within 6 months after breast cancer diagnosis were enrolled, and the effect of multimodality treatment on the risk of BCRL was analyzed using the Cox proportional-hazards model. Multimodality treatment administered through six months of treatment was grouped as only Surg; Surg/Chemo; Surg/ Chemo/Radio; Surg/Radio; only Chemo; and Chemo/Radio. Results The risk of BCRL was higher in the Surg/Chemo group (hazard ratio [HR]: 1.54, 95% confidence interval [CI]: 1.43–1.65), Surg/Chemo/Radio group (HR: 1.51, 95% CI: 1.43–1.65), only Chemo group (HR: 1.58, 95% CI: 1.45–1.71), and Chemo/Radio group (HR: 1.13, 95% CI: 1.00–1.29) in comparison with the only Surg group. Conclusion BCRL occurrence is an after-effect of complex breast cancer treatments, and the risk may vary depending on the treatment method, including Surg, chemo, and radio. Our findings suggest that multidisciplinary strategies are required to minimize the risk of BCRL development in patients with breast cancer.